PENGARUH KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN KONSUMEN STUDY PADA HOTEL PANDANARAN SEMARANG - Dias Widyarto; Wahyu Hidayat; Reni Shinta Dewi (Universitas Diponegoro, 2013)
Development of service industries, especially the hospitality industry today is one business that began in great demand by investors in Indonesia. With the improving economic growth and make the hotel business is not only to meet the accommodation needs of tourists, but also used as a lobby, parties, weddings, seminars and accommodation both business and government activities. For any guests or customer service quality factor, and price become the benchmark in customer satisfaction. The existence of good service, and the appropriate price will have an impact on customer satisfaction made​​. Good customer satisfaction will impact on hotel room occupancy rate increased. This study aimed to determine how much influence the service quality, and price to customer satisfaction on Hotel Pandanaran Semarang either partially or simultaneously. This type of study is explanatory research. Data collecting technique using questionnaire distributed to 100 respondents as service users of Hotel Pandanaran Semarang. Sampling technique using purposieve sampling. Data analysis technique using linear regression analysis. The research suggests that company should improvement of service quality in terms of the skills of the employee in completing the work by conducting training. In terms of price to be adjusted between room rates, room types and amenities. In terms of customer satisfaction should be augmented security personnel to enhance the sense of security and comfortincrease